Treatment of refractory vasospastic angina complicated by acute pulmonary oedema with levosimendan: a case report. Issue 1 (5th February 2019) - Moltrasio, Marco; Cosentino, Nicola; Conte, Edoardo; Campodonico, Jeness; Marenzi, Giancarlo
Abstract: Background: Vasospastic angina (VA) is an important cause of chest pain and patients often have 3- to 6-month clusters of recurrent attacks, separated by relatively asymptomatic periods. During these episodes the resulting myocardial ischaemia can lead to clinical complications of different severity, including acute myocardial infarction, acute heart failure, and cardiogenic shock. The management of severe and recurrent VA attacks is challenging, and no specific recommendations exist in recent cardiologic guidelines on the pharmacological strategy (inotropic/vasopressor agents) to adopt for this acute clinical setting. Case summary: We present a case of recurrent episodes of VA complicated by acute pulmonary oedema and cardiogenic shock despite maximal tolerated therapy (intravenous calcium antagonist and nitrates) that was successfully treated with levosimendan. Discussion: Levosimendan rapidly reverted cardiogenic shock, acute pulmonary oedema, and mitral regurgitation caused by a refractory coronary spasm, contributing to persistent clinical stabilization. Further evidence and a longer follow-up are needed to support our observation on the efficacy of levosimendan in this specific clinical setting.